SISTEM INFORMASI PERPUSTAKAAN DIGITAL PADA SMP NEGERI 2 SIMPANG EMPAT - Anggi Natasya Br. Batubara; Resianta Perangin-angin; Eviyanti Novita Purba (Universitas Methodist Indonesia, 2023)
SMP Negeri 2 Simpang Empat is a junior high school located on JL. Simpang Empat, Ndokum Siroga, Berastagi, Karo Regency. At the current library of SMP Negeri 2 Simpang Empat, it is still done conventionally, namely data handling is still done by way of copying books, which invites data input, which takes a long time and cannot be opened easily and quickly. Therefore, with the existence of a digital library information system that intends to deal with the problems seen in SMP Negeri 2 Simpang Empat, in paying attention to these problems, a system that can process data in the library is needed. The programming languages ​​used are: PHP and MYSQL Database. The existence of a digital library information system at SMP Negeri 2 Simpang Empat can make it easier for students to find books quickly and easily and save time, save energy, save space, save costs in obtaining information.